Resfriamento evaporativo: estudo do potencial de sua aplicação no Brasil - Carossi, Gilmar de Assis Borges (2006)
The objective of this work is the validation of a mathematical method that will be used for the map of the Brazilian areas with potentiality of using systems of evaporative cooling in the conditioning of atmospheres. The cooler rehearsed evaporative presents capacity for conditioning of an atmosphere of up to 50 m2. Climatic maps of the temperatures are put upon and of the relative humidity of the air in Brazil, making possible the characterization of the areas where the temperature conditions and relative humidity of the air are inside of values susceptible to use of evaporative systems. The climatic data of temperature and relative humidity of the air acquired in this over-position were used as entrance in the mathematical model, that it supplied the exit data, that were analyzed and discarded the areas whose values of the temperature and relative humidity of the air are not inside of the parameters of thermal comfort. Like this the climatic map of Brazil is had where the evaporative system has potential of being used, month to month and for each state. Concepts on psychrometry and evaporative cooling are approached in this work. The results of this work collaborates with the researches on the use of systems evaporative in Brazil, and it informs about the market capacity to be explored with that type of conditioning of atmospheres.